2007
DOI: 10.5650/jos.56.269
|View full text |Cite
|
Sign up to set email alerts
|

Ester Quats: The Novel Class of Cationic Fabric Softeners

Abstract: Esterquats, which are quaternary ammonium compounds having two long (C(16)-C(18)) fatty acid chains with 2 weak ester linkages, represent a new generation of fabric softening agents, having replaced the dialkyldimethylammonium salts (e.g. DTDMAC and DSDMAC). The inclusion of ester linkages into the aliphatic chains has significantly improved the kinetics of biodegradation of the cationic surfactants, lowering the environmental exposure levels. This new generation of fabric softening agents combines a good envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 13 publications
(7 reference statements)
0
48
0
2
Order By: Relevance
“…Esterquats synthesized by esterification of triethanolamine with two equivalents of fatty acid give a thermodynamicallycontrolled statistical distribution of mono-, di-, and triesters, which commercially are quaternized with dimethyl sulphate [3]. It has been reported that esterquats establish a cleavable functionality within the "twin tails", which enhance their biodegradability by separating the positively charged nitrogen hydrophile from the hydrophobic part.…”
Section: Introductionmentioning
confidence: 99%
“…Esterquats synthesized by esterification of triethanolamine with two equivalents of fatty acid give a thermodynamicallycontrolled statistical distribution of mono-, di-, and triesters, which commercially are quaternized with dimethyl sulphate [3]. It has been reported that esterquats establish a cleavable functionality within the "twin tails", which enhance their biodegradability by separating the positively charged nitrogen hydrophile from the hydrophobic part.…”
Section: Introductionmentioning
confidence: 99%
“…Typical fabric softener formulations consist of about 15% of a cationic surfactant, such as triethanolamine (TEA)-esterquats of fatty acids [40,41], in water. For the measurements, conjugates 13-16 were dissolved in ethyl acetate at a concentration to potentially release a total of 8.7 mg (0.05 mmol) of δ-damascone.…”
Section: Performance On Fabricmentioning
confidence: 99%
“…This new type of fabric softening agent combines a good environmental profile with the structural features required for an effective fabric conditioner 1,2 . Esterquat cationic surfactant is one of the biodegradable fabric softener due to the presence of ester linkage 3 .…”
Section: Introductionmentioning
confidence: 99%